Bibliometric Analysis and Literature Review of Islamic Religious Education Curriculum Model - Salman, Nola Fibriyani Bte; Arvita, Rizky Firda; Inayati, Nurul Latifatul; Apriantoro, Muhamad Subhi (Journal of Educational Management and Strategy, 2024)
This study aims to determine the mapping of the development and direction of Analysis Curriculum Islamic Education research in publications indexed by Scopus. This study used bibliometric analysis techniques to explore all publications indexed in Scopus' database of Analysis Curriculum Islamic Education from 2004 to 2023. The data obtained were analyzed using Excel and R/R-Studio. VOSviewer is used to perform visual analysis of the simultaneous occurrence of keywords and document citations. The author found 209 publications that fit the function, subject, and criteria set. The results of this study show an annual growth rate of 8.84%, with the most publications on Analysis Curriculum Islamic Education in 2021. Indonesia is the country that contributes the most publications with affiliations from Universitas Islam Negeri Ar-Raniry. Avirsais, O. become the most prolific writer in the theme Analysis Curriculum Islamic Education. The bibliometric analysis performed was limited to Scopus data. Other national and international databases were not taken into account in the study. This study presents a brief overview of the literature accessible to researchers working in education and provides recommendations for future research.